PENERAPAN METODE MENGAJAR KOLABORASI UNTUK PENINGKATAN KETERAMPILAN MEMBACA BAHASA MANDARIN SISWA PENDIDIKAN DASAR - Robby Anto, Rachelia Giovanny; Ginting, Daniel (Jurnal Visi Ilmu Pendidikan, 2024)
Collaborative learning is a process whereby learners with varying abilities work together in small groups to achieve a common goal. This approach emphasizes the importance of students working together to construct knowledge and develop concepts to solve problems or tasks assigned by the teacher. This study employed a classroom action research methodology to improve Mandarin reading ability of second-grade students in an elementary school in Banyuwangi Regency. The participants were twenty-three students aged eight years old. The increase in student performance was attributed to the higher intensity of exercises in the second cycle. Collaborative learning facilitated the achievement of learning outcomes by allowing students to work together and construct knowledge.